HUBUNGAN ANTARA PENGETAHUAN MASYARAKAT DAN KETERSEDIAAN FASILITAS SANITASI DENGAN KEPATUHAN CUCI TANGAN PAKAI SABUN PADA MASA PANDEMI COVID-19 DI MATA AIR KUNDUR - Faizal Rangkuti, Ahmad; Mardalena (Universitas Ahmad Dahlan, 2023)
COVID-19 is a fast-spreading infectious disease. In Indonesia, there are 3,372,374 confirmed positive cases of COVID-19, while in the Riau Islands Province, Karimun Regency, 5,293 cases as of September 2021. Washing hands with soap can prevent transmission of COVID-19 among the community. This study aims to determine the relationship between knowledge and availability of sanitation facilities with handwashing compliance with soap during the COVID-19 pandemic. This study uses a quantitative approach with a cross sectional study design. The number of samples used as many as 62 respondents who were selected using probability sampling technique. The results showed that people who have a good level of compliance (36.6%) good knowledge of (27.4%), availability of good sanitation facilities (37.1%) and a high level of education (69.4%). Based on the results of statistical tests, the relationship between knowledge, availability of sanitation facilities and education level with handwashing compliance with soap each has a p-value of 0.004-0.049 and 0.019 (p<0.005). Knowledge, availability of sanitation facilities and level of education have a significant relationship with handwashing compliance with soap. It is recommended for the entire community of RT 013 to increase knowledge about hand washing with soap in order to improve compliance behavior in washing hands with soap during the COVID-19 pandemic.